PELATIHAN DZIKIR UNTUK MENURUNKAN KECEMASAN IBU HAMIL PERTAMA - Usdati Mardhiyah; Nuristighfari Masri Khaerani (UIN Sunan Kalijaga, 2017)
This research aims to find out the influence of dhikr training to reduce anxiety in first pregnant women. The method used in this research is one group pre-test post-test design by giving treatment in the form of dhikr training. Subjects in this research get dhikr training which is arranged based on dzikir aspect. The sample technique used in this research is purposive sampling technique with the total subjects of four of first pregnant woman. The writer uses anxiety scale as the data colection. Analysis of differences in pre-test and post-test values using Wilcoxon Signed-Rank Test technique. The result of analysis shows the value p = 0,034 (p <0,05). Dhikr training can reduce anxiety in first pregnant women.